Microburst Scale Size Derived From Multiple Bounces of a Microburst Simultaneously Observed With the FIREBIRD‐II CubeSats. Issue 17 (14th September 2018) - Shumko, Mykhaylo; Sample, John; Johnson, Arlo; Blake, Bern; Crew, Alex; Spence, Harlan; Klumpar, David; Agapitov, Oleksiy; Handley, Matthew
Abstract: We present the observation of a spatially large microburst with multiple bounces made simultaneously by the Focused Investigation of Relativistic Electron Bursts: Intensity, Range, and Dynamics II (FIREBIRD‐II) CubeSats on 2 February 2015. This is the first observation of a microburst with a subsequent decay made by two coorbiting but spatially separated spacecraft. From these unique measurements, we place estimates on the lower bounds of the spatial scales as well as quantify the electron bounce periods. The microburst's lower bound latitudinal scale size was 29 ± 1 km and the longitudinal scale size was 51 ± 1 km in low Earth orbit. We mapped these scale sizes to the magnetic equator and found that the radial and azimuthal scale sizes were at least 500 ± 10 km and 530 ± 10 km, respectively. These lower bound equatorial scale sizes are similar to whistler mode chorus wave source scale sizes, which supports the hypothesis that microbursts are a product of electron scattering by chorus waves. Lastly, we estimated the bounce periods for 200‐ to 800‐keV electrons and found good agreement with four common magnetic field models. Plain Language Summary: Microbursts are a subsecond impulsive increase of electron precipitation from the outer Van Allen radiation belt into the atmosphere, believed to be an important loss process of radiation belt electrons. Here we present an observation of a microburst observed simultaneously by the twin Focused Investigation of Relativistic Electron Bursts: Intensity, Range, and Dynamics II CubeSats. This unique observation allowed us to calculate the microburst's spatial scale size and electron bounce periods. The spatial scale size in low Earth orbit was found to be a few tens of kilometers in size, one of the largest reported in literature. We then magnetically mapped this scale size to the region near the microburst's generation region and found it to be around 500 km, similar to the spatial scale size of the waves that are believed to be responsible for microburst generation. This observation shows an example of how large microbursts can be, and it sheds light on its scattering mechanism. Key Points: Multiple bounces from a microburst were observed by the two FIREBIRD‐II Cube‐Sats at LEO The lower bounds on the microburst scale size at LEO were 29 ± 1 km (latitudinal) and 51 ± 11 km (longitudinal) Deduced lower bound equatorial scale size was similar to the whistler mode chorus source scale